Developing digital module of intermediate writing subject in virtual class (V-Class) unila learning management system in English Education Study Program University of Lampung - Sholihah, Lilis (Universitas Lampung, 2023)
At Lampung University, English Education Study Program, Faculty of Teacher Training and Education, there are several issues that concern the author, one of which is the digital module for online learning that is not yet available. Therefore, the author made the idea to develop a Digital Module on the UNILA Virtual Class (V-Class) LMS for the Intermediate Writing Course of the English Education Study Program.1) Conducting a survey of students which is divided into three stages of activity, namely, making a questionnaire, distributing questionnaires, and analysing questionnaires. 2) Conducting literature review 3) Developing e-RPS. 4) Making digital modules. 5) Determining the validator who will validate the digital module. 6) Validation of digital modules (expert judgment). 7) Finalization and socialization of digital modules 8) Evaluation and follow-up. The development of Digital Modules on the UNILA V-Class LMS for the Intermediate Writing Course of the English Education Study Program has several impacts, individually it is able to improve technical competence and provide learning innovations. In groups, learning outcomes can be achieved maximally, effectiveness in online learning, and increase student motivation. Organizationally, it can improve the quality of the institution and increase public trust in the institution. The actualization activities carried out are the development of digital modules for the Intermediate writing course of the University of Lampung English Education Study Program which consists of eight activities, as well as efforts to make video which is integrated with other materials that can be uploaded in LMS V-Class Unila. Besides, the learning contract/course outline and lesson plan (e-RPS) were appropriately made and adapted with the new curriculum and the situation while fighting pandemic era. This research was done as a report of the implementation of the actualization of basic training participant which implemented basic values of the civil servant. The hope is that there is an internalization of the basic values of ASN into the author and can also implement the role and position of Civil Servant (ASN) in the Republic of Indonesia.